PENGARUH GAYA HIDUP, LABEL HALAL DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SCARLETT WHITENING (STUDI KASUS SISWI SLTA DI KECAMATAN SUNGAI RUMBAI) - Nurdiana Nurdiana; Mayroza Wiska; Dini Elida Putri (Universitas Sarjanawiyata Tamansiswa, 2022)
Scarlett Whitening is a body care product that has many product lines, namely skin care and body care. This research was conducted to determine the effect of lifestyle, halal label and price on purchasing decisions for scarlett whitening products (a case study of high school students in Sungai Rumbai sub-district). This study used a quantitative method of collecting data using a questionnaire, the respondents who were used as samples were 200 respondents. The results of this study indicate that lifestyle variables have no significant effect on purchasing decisions for scarlett whitening products. With the results of the t-test for lifestyle variables, it can be seen that the t-count is 1.433 and the t-table is 1.652 where the t-count is smaller than the t-table (1.433 <1.652). This shows that the independent variable of lifestyle has no significant effect on the dependent variable on purchasing decisions. While the halal label variable has a positive and significant effect on purchasing decisions for Scarlett Whitening products. With the results of the t-test, it can be seen that the t-count is 2.745 and the t-table is 1.652 where the t-count is greater than t-table (2.745> 1.652). This shows that the independent variable halal label has an effect on the dependent variable on purchasing decisions. And the level is significantly greater than than alpha (0.007<0.05). The price variable has a positive and significant effect on purchasing decisions for scarlett whitening products, with the results of the t-test t-count 10.383 and t-table 1.652 where t-count is greater than t-table (10.383 > 1.652) This shows the independent variable has a positive effect on the dependent variable of purchasing decisions. However, lifestyle variables (X1), halal label (X2) and price (X3) together have a significant effect on purchasing decisions (Y). Its Adjusted R Square value is 56.8%. This shows that purchasing decisions are influenced by lifestyle variables, halal labels and prices, while the remaining 43.2% is influenced by other factors not examined in this study.